Regulation and biosynthesis of secondary metabolites. XVIII. Adenylate level and chlorotetracycline production in Streptomyces aureofaciens - Curdová, E; Kremen, A; Vanĕk, Z; Hostálek, Z (Folia microbiologica, 1976)
The relationship was studied between the energy metabolism of the actinomycete Streptomyces aureofaciens and the biosynthesis of chlorotetracycline by this organism. The energy charge values in a culture of low-production strain were almost identical with those of a production variant but the total sum of adenylates was about 10 times higher. In the stationary growth phase both strains evinced a drop in energy charge values followed by a rise to the original level. An increase in the concentration of inorganic phosphate in fermentation medium caused a suppression of antibiotic formation in the lowproduction strain and further rise in the total adenylate level. The expression of the energy charge in Streptomyces aureofaciens acquires a complex character owing to the participation, apart from the adenylate system, of high-molecular polyphosphates as energy donors and the probable lack of a regulating mechanism such as the adenylate kinase reaction.
Keywords: adenosindifosfát; fosfáty; genetická variace; Streptomyces aureofaciens; Genetic Variation; adenosintrifosfát; Adenosine Triphosphate; Energy Metabolism; Adenosine Diphosphate; Adenosine Monophosphate; energetický metabolismus; Chlortetracycline; adenosinmonofosfát; chlortetracyklin; Adenine Nucleotides; Phosphates; adeninnukleotidy